Values of Da’wah in Aceh Tradition (Case Study of Lueng Keubeu Samalanga Village) - Halimatussa’diah (Britain International of Humanities and Social Sciences (BIoHS) Journal, 2020)
In this study, the writer raised three main problems, namely: traditional forms in Lueng Keubeu village community, types of da'wah values ​​in Acehnese customs and factors inhibiting the implementation of da'wah through Acehnese adat. This study uses a qualitative descriptive method using interview and observation techniques. In addition, the writer also uses a literature approach. The source of the data that the author uses in this study is the result of observations on the object of research, namely the village of Lueng Keubeu and the respondents who provide information (data) about the core of this problem. From the results of this study it can be seen that there are several customs in the Lueng Keubeu community: tron ​​ublang (down to the ground), meukawen (marriage), peutron aneuk (children's land), sykuran (thanksgiving) meulikee customs (Maulid memorial), Meureukon custom (a kind of barzanji). During this time the customs contained in the village of Lueng Keubeu do not conflict with the Shari'a, and these customs contain the values ​​of da'wah.